Effect of operating parameters on anaerobic (upflow) filter performance - Koirala, Ramesh; Vigneswaran, Saravanamuthu; Hanaki, K.; Samorn Muttamara; Royal Government of the Netherlands (Bangkok : Asian Institute of Technology, 1987)
A laboratory- scale AF was studied to find the effect of various design parameters i.e. hydraulic loadings & hydraulic retention times , influent concentrations and filter depths on the performance of AF. The AF was fed with commercial grade glucose synthetic waste. The effects of the se de sign parameters were measured in terms of COO removal efficiency and gas production . The ratio of methane to carbon dioxide in the gas produced was also found out by using Gas Chromatograph (Sichromat 2 , made in Germany), The COO removal efficiency decrease d with the increase in hydraulic loading. The gas produced per kg of COO removed also decreased with the increase in hydraulic loading. The inverse relationship proposed by YOUNG and McCARTYC1 968) did not exist in higher values of HRTs C144-24h) . But , it held good after a HRT value of 24h up to 6h. Hence , a relations hip , based on the regression analysis of experimental values , was proposed between the COO removal efficiency an d the HRT for HRT range of 24-6h. The gas production was also affected by the variation of HRT values . The change in influent concentration at a constant hydraulic loading did not have significant effect on the COO removal efficiency and gas production capacity of the AF. It did not show any significant effect on the methane content or gas al so. A filter depth of 120 cm was found to be sufficient enough to provide COO removal efficiency of 97 . 2- 72.2% at hydraulic loading range of 0.11 -2.7 m3 /(n12 .d) and an average influent concentration of 3000 mg/L of synthetic waste (glucose being the ma in substrate) {u2022}
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Sewage -- Purification -- Filtration